A new flavonoid, a new phenylethanoid glycoside and related compounds isolated from the inflorescences of Plantago lanceolata L. Issue 15 (1st August 2022) - Budzianowska, Anna; Budzianowski, Jaromir
Abstract: For the first time inflorescences of a plant species from the genus Plantago (Pantaginaceae)— Plantago lanceolata L. (Ribwort Plantain), a known medicinal plant, were subjected to studies of phenolic compounds, which resulted in an isolation of two new compounds: a flavonoid—isorhamnetin 3- O -α-L- 4 C1 -arabinopyranosyl-(1→2)-β-D- 4 C1 -glucopyranoside) (1 ) and a phenylethanoid glycoside—2-(3, 4-dihydroxyphenyl)ethyl O -α-L-arabinofuranosyl-(1→2)-[α-L- 1 C4 -rhamnopyranosyl-(1→3)][ E -caffeoyl-1→4]-β-D- 4 C1 -glucopyranoside (14 ), along with fourteen known compounds—eight flavonoids (2–9 ) and six phenylethanoid glycosides (10–13, 15–16 ). The chemical structures were established by 1 D and 2 D NMR and HRESIMS spectral methods. The known phenylethanoids were the same as reported for leaves or aerial parts of P. lanceolata or other Plantago species. The flavonoids appeared to be only flavonols, mainly isorhamnetin 3- O- and 3, 4'- O - glycosides, and thus completely different from flavones, mainly luteolin and apigenin glucuronides, previously reported in the leaves. The possible medicinal and chemotaxonomic relevance of the phenolics found in P. lanceolata inflorescences were taken into consideration. Graphical Abstract: UF0001